Analisis Sentimen Terhadap Pembelajaran Tik Berdasarkan Data Kritik Saran Siswa Menggunakan Metode Naive Bayes Studi Kasus : SMPK Dominikus Gollu Pande - Marselinus bulu; Elfira Umar; Martinus Malo Ngongo (Jurnal Pendidikan, Sains Dan Teknologi, 2023)
Teacher teaching quality is the key to the success of education in the institution of education by having teachers who are able to teach well to create high-value children of the nation., Especially in the eyes of the technology of information..In order to get teachers that fit academic standards, certainly need to do an evaluation on the eyes of information technology climbers..Therefore smpk dominikus gollu pande do questionnaires with criticism form advice that students can fill.Current, data criticism of advice has not been used to analyze and evaluate the process of learning.That's why., In this study, there's been a sentimental analysis of the results of the criticism that students have sent., to know the criticism of the suggestion is of positive value, negatif.Salah satu metode analisa sentimen yang dapat digunakan untuk menyelesaikan masalah opinion mining adalah metode naive bayes.Data accumulates as much as 100 data at a semester's span, Which is